Comparison of Conventional and Rotary Files in Root Canal Preparation of Primary Molar Teeth - Maleeha Ijaz, Aden Imran, Alisha Jamil, Ariffullah Khan, Ihtesham ud Din, Syeda Faiza Gilani (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Pulpectomy is a very common pulp therapy provided to the primary molars with necrosis and irreversible pulpitis. Conventional (hand) files have been used as a standard meth- od of root canal instrumentation in primary teeth. But, being a time-consuming technique, it has led to an increase in the chairside time henceforth, can result in a decrease of co- operative behaviour in paediatric patients. Objective: The aim of the study was to compare chairside time in root canal preparation of primary teeth clinically using rotary and hand files and quality of obturation radiographically. Methodology: The study was designed as non- probability consecutive sampling performed at a single centre on 108 primary molars with necrosis or irreversible pulpitis in children aged 4-9 years. Subject selection for our study was in accordance with the inclusion and exclusion criteria and were placed randomly in the two groups i.e. (HF) conventional (hand) files and (RF) rotary (ProTaper NEXT®) file groups respectively. Results: A total 108 primary molars were included in the study. There was a significant difference (p=0.003) between Group RF and Group HF for root canal preparation time (mins). On the other hand, there was no difference in the quality of obturation among the two groups HF & RF (94.4% vs 96.3%) (p=0.31). Conclusion: The study concluded that mean root canal preparation time (mins) was significantly reduced in rotary file group as compared to the hand file group. But the results in quality of obturation was similar for both techniques. Keywords: Hand files, Primary molars, Pulpectomy, Rotary (protaper).